Aplikasi Indonesian News Aggregator Berbasis Android yang Didukung oleh Sistem Perekomendasi - Wahono, Nydia Valentina; Wibowo, Adi; Intan, Rolly (Jurnal Infra, 2015)
Internet technology has shown its significant growth. It affects human habits in how they seek and gather information. News has become humanâs daily needs. There are so many kind of news to be read, but time is limited. Therefore, recommendation feature for news feature nowadays is needed, so it is easier to supply what kind of news that readers read, where user can rate the news.These research focused on recommendation feature for news feature based on Android. To give recommendation feature, there will be a certain server required to grab news data from some specific websites. Then, news data which was grabbed is parsed and processed to be used for members profile calculation.Based on the research, rating can change news recommendation which is given from time to time and there are still some flaws on HTML structure and RSS standard from Indonesian news websites.